Strategi Guru dalam Menangani Siswa Lamban Belajar di MI Muhammadiyah 2 Kedungbanteng - Hartanti, Regista Dwi Adi; indrakurniawan, machful (WASIS : Jurnal Ilmiah Pendidikan, 2024)
This study aims to describe the teacher's strategy in dealing with slow learner students at MI Muhammadiyah 2 Kedungbanteng.The research method used is descriptive qualitative. The research was conducted at MI Muhammadiyah 2 Kedungbanteng, Sidoarjo, using data collection techniques of observation, interview, and documentation. Data analysis refers to the Milles and Huberman analysis model, which includes data reduction, data display, verification, and conclusion drawing stages. Data validity was tested using triangulation techniques. The results show that teachers apply effective strategies in dealing with slow learners, including motivation, selection of appropriate learning media, flexibility in material delivery, repetition, and personal approach. By providing praise, simple explanations and individualized guidance, teachers succeeded in helping slow learners achieve success and increase their intrinsic motivation. Overall, a responsive and flexible approach to learning plays an important role in improving the achievement of students with learning difficulties at the elementary school level.